A survey on ACO based multipath routing algorithms for ad hoc networks. Issue 4 (6th November 2017) - Sharma, Ishu; Ramkumar, K.R.
Abstract : Purpose: The purpose of this paper is to review the existing routing algorithms for wireless ad hoc networks to evaluate the methods according to the current requirements. Wireless ad hoc network can provide communication in emergency situations. Active nodes in ad hoc network work as sender, receiver and router at the same time. Nodes are equipped with limited bandwidth and energy. Optimal routing method can help in "smart use" of available resources. Evolvement of routing method based on need is a continuous process. Numerous applications of ad hoc network motivates researcher for further development to fulfill the need of society. Design/methodology/approach: In this paper, routing algorithms for ad hoc network based on ant colony optimization, multipath routing and with multiple input multiple output (MIMO) antenna support have been discussed. Findings: Comparative analysis has been drawn among existing algorithms of different categories. Transmitting message packets parallel through multiple paths in the network can save overall resource usage in the network. Originality/value: The authors have discussed the future area of development for optimal routing in ad hoc networks. Considering signal noise ratio and congestion status while selecting path can provide better energy use in the network. Rather than leaving less prioritized route paths, multiple paths can be used for sending data packets parallel.